THE CONTENT OF THE MIGHTY MOVEMENT AND ITS EDUCATIONAL SIGNIFICANCE IN HISTORY LESSONS - Kewlimzhaev Turdibek (Western European Studies, 2024)
The essence of Jadidism is an intense and exciting process from understanding the Nation and Homeland to fighting for their benefit. This movement also educated the nation. Our forefathers understand that the nation must first be free and independent in order to live and develop, and they pay special attention to the awakening of a peaceful people.
Keywords: School; education; youth; literature